2011
DOI: 10.1152/ajpendo.00626.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HIF-1α activity in adipose tissue by obesity-associated factors: adipogenesis, insulin, and hypoxia

Abstract: The transcription factor HIF-1α activity is increased in adipose tissue to contribute to chronic inflammation in obesity. However, its upstream and downstream events remain to be characterized in adipose tissue in obesity. We addressed this issue by investigating adipocyte HIF-1α activity in response to obesity-associated factors, such as adipogenesis, insulin, and hypoxia. In adipose tissue, both HIF-1α mRNA and protein were increased by obesity. The underlying mechanism was investigated in 3T3-L1 adipocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 64 publications
7
129
0
Order By: Relevance
“…In many of the pathological situations described above (5,7,8,12,16,17), HIFs are activated in response to the hypoxic and inflammatory microenvironment. HIFs represent the primary O 2 -sensing transcription factors (18)(19)(20)(21) as heterodimers comprised of an O 2 -sensitive α subunit (HIF-α) and a constitutively expressed β subunit (HIF-1β or aryl hydrocarbon receptor nuclear translocator [ARNT]).…”
Section: Hypoxia and Hypoxia-inducible Factorsmentioning
confidence: 99%
“…In many of the pathological situations described above (5,7,8,12,16,17), HIFs are activated in response to the hypoxic and inflammatory microenvironment. HIFs represent the primary O 2 -sensing transcription factors (18)(19)(20)(21) as heterodimers comprised of an O 2 -sensitive α subunit (HIF-α) and a constitutively expressed β subunit (HIF-1β or aryl hydrocarbon receptor nuclear translocator [ARNT]).…”
Section: Hypoxia and Hypoxia-inducible Factorsmentioning
confidence: 99%
“…Since the increase in vascular density is essential for adipose tissue expansion, with endothelial cells actively promoting the development of preadipocytes and growth of mature adipocytes, apelin has been proposed to contribute to the development of new vasculature in expanding fat depot [149] . Several studies have demonstrated that apelin is a potent angiogenic factor [149] , grossly equivalent to vascular endothelial cell growth factor and, like other angiogenic factors, its gene is upregulated under hypoxia condition [150] . Hypoxia induces expression and secretion of apelin in both human and murine adipocytes, through the hypoxia-inducible transcriptor factor 1a.…”
Section: Apelinmentioning
confidence: 99%
“…HIF-1␣ is a primary transcription factor that is activated by hypoxia to regulate gene expression, although HIF-1␣ is also regulated by insulin and adipogenesis in obesity (17). To test the role of HIF-1␣ in the regulation of 11␤-HSD1 expression, we compared 11␤-HSD1 expression in WT and HIF-1␣-null MEFs in this study.…”
Section: ␤-Hsd1 Is Inducted By Nf-bmentioning
confidence: 99%